Effects of sensorimotor foot orthoses on static balance in healthy adults: a crossover randomized controlled trial - Becker, Stephan; Simon, Steven; Hayer, Josefine; Heidger, Jana; Koltschin, Wjatscheslaw; Dindorf, Carlo; Dully, Jonas; Fröhlich, Michael (Frontiers in Sports and Active Living, 2025)
BackgroundSensorimotor foot orthoses (SMFO) may be a helpful intervention to improve balance by enhancing proprioceptive input within the sensorimotor control loop. SMFO intervention could have beneficial effects on reducing risk of ankle sprains and falls.MethodsA total of 57 healthy adults (age: 48.5 ± 11.8 years) completed a static balance test (30 s) on a force plate, with open eyes (OE) and closed eyes (CE). Balance performance was assessed by using posturography to measure the sway area (mm2), under SMFO and no foot orthoses (NFO) conditions.ResultsDescriptive statistics show a reduced median of 1.9 cm2 (29.6%) for SMFO with CE. No interaction was found, while main effects showed significant differences (vision: p < 0.001, sole: p = 0.004). post-hoc tests underlined these results and static balance improved by a median 0.8 cm2 (14.5%) with SMFO compared to NFO.ConclusionThe SMFO seems to support static balance and sensorimotor system, which could help to avoid falls and injuries as ankle sprains. Further age groups, long-term effects and the impact on dynamic balance must be studied.